Antibacterial Activity of Vernonia amygdalina Leaf Extract and Fraction against the Growth of Escherichia coli Bacteria - Norainny Yunitasari; Nastiti Trikurniadewi; Arum Sani Hidayah; Herlina Deka Putri Harjo; Ananda Aulia Nazihah (Journal of Food and Pharmaceutical Sciences, 2026)
Vernonia amygdalina leaves are known to possess antibacterial activity, which is commonly evaluated using ethanol extracts. However, solvent polarity plays a crucial role in extracting secondary metabolites that contribute to antibacterial effects. This study aimed to evaluate the antibacterial activity of Vernonia amygdalina leaf extracts obtained using different solvents. The extraction was performed by maceration using methanol and ethyl acetate. Three maceration processes were conducted using the same amount of leaf powder: methanol (M1), ethyl acetate (M2), and methanol followed by fractionation (M3). The M3 extract was further fractionated using n-hexane and ethyl acetate. Antibacterial activity was tested using the disc diffusion method. The results showed that M1 and the ethyl acetate fraction of M3 exhibited higher antibacterial activity than M2, as indicated by inhibition zone diameters of 8.56 mm (M1), 5.50 mm (M2), and 7.71 mm (M3). These differences are likely due to variations in the types and amounts of secondary metabolites extracted by each solvent. Further studies are recommended to investigate the correlation between secondary metabolite content and antibacterial activity of Vernonia amygdalina and other herbal plants.